Petrology and geochemistry of Devono-Carboniferous volcanic rocks in Nova Scotia - Dostal, J.; Keppie, J.; Dupuy, C. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1983)
The Devono-Carboniferous volcanic rocks of Nova Scotia include Middle Devonian basalts from the McAras Brook Formation in the northern Antigonlsh Highlands (Ballantynes Cove and McAras Brook areas), Kiddle Devonian and Carboniferous basalts and rhyolites of the Fountain Lake Group In the Cobequid Highlands and the Upper Devonian-Lower Carboniferous basalts and rhyolites of the Fisset Brook Formation in Cape Breton Island. The volcanic rocks were extruded upon the continental crust in an lntraplate setting. The basalts are tholelitic except those from Ballantynes Cove which are alkaline. All these basalts could have been derived from a similar upper mantle source - garnet peridotite. Rhyolites were probably generated by crustal anatexis related to the ascending basaltic magma. The Devono-Carboniferous volcaniant is probably connected with rifting along faults bounding the Magadalen pull-apart basin. In the Cobequid Highlands, the volcanlsm appears to be spatially and temporally associated with plutonlsm.